177k views
2 votes
Put the quadratic into vertex form and state the coordinates of the vertex. y= y= \,\,x^2-6x-3 x 2 −6x−3

1 Answer

4 votes

Answer:


y = (x - 3)^2 - 12


(3,-12)

Explanation:

Given


y = x^2 - 6x - 3

Solving (a): In vertex form

The vertex form of an equation is:


y = a(x - h)^2 + k

To do this, we make use of completing the square method.

We have:


y = x^2 - 6x - 3

------------------------------------------------------------------

Take the coefficient of x (i.e. -6)

Divide by 2; -6/2 = -3

Square it: (-3)^2 = 9

Add and subtract the result to the equation

------------------------------------------------------------------


y = x^2 - 6x - 3


y = x^2 - 6x + 9 - 9 - 3


y = x^2 - 6x + 9 - 12

Factorize
x^2 - 6x + 9


y = x^2 - 3x-3x + 9 - 12


y = x(x - 3)-3(x - 3) - 12

Factor out x - 3


y = (x - 3)(x - 3) - 12

Express as squares


y = (x - 3)^2 - 12

Hence, the vertex form of
y = x^2 - 6x - 3 is:
y = (x - 3)^2 - 12

Solving (b): State the coordinates of the vertex.

In
y = a(x - h)^2 + k; the vertex is: (h,k)

The vertex of
y = (x - 3)^2 - 12 will be
(3,-12)

User Jay Nebhwani
by
5.4k points